Synoptic Conditions of Droughts and Dry Winds in the Black Sea Steppe Province Under Recent Decades - Semenova, Inna; Slizhe, Mariia (Frontiers in Earth Science, 2020)
The features of regional atmosphere circulation, which accompanied simultaneously by two high impact hydrometeorological phenomena such as droughts and dry winds in the Black Sea Steppe zone of Ukraine were considered. Dry wind as a complex phenomenon is widespread throughout Ukraine during warm season of the year. Dry winds often accompany a drought, but they appear as peripheral processes in contrast to the droughts, which usually are formed in central parts of anticyclones. The number of days with dry wind at the Steppe stations varies in average from 10-20 cases to 40-50 cases per warm season, while in the coastal zone the number of days decreases sharply due to common increase of air relative humidity. Analysis of the interannual dynamics of dry winds showed that the number of days with dry wind increases significantly in seasons characterized by a high aridity, according to values of used drought index. Two time intervals with high and low frequency of seasonal droughts and dry winds were detected during the considered period 1995-2015. These phenomena have become more intense after 2004, compared to the previous decade. Backwards trajectories of air particles shown that the most cases of dry winds origin in air masses, which forming at surface level to the east or north-east outside the territory of Ukraine and pass to study area during five days.